Description of the female of Leptagrion jeromei Lencioni, Vilela & Furieri, 2021 (Odonata: Coenagrionidae) with taxonomic notes on the male - Farias, Antonio Bruno Silva; Santos, Jean Carlos (Zootaxa, 2024)
The female of Leptagrion jeromei Lencioni, Vilela & Furieri, 2021 is described, illustrated, and diagnosed based on a specimen collected in epiphytic bromeliads at the Federal University of Sergipe (♀ (B0545), BRAZIL, Federal University of Sergipe, São Cristóvão, -10.92707, -37.10100, 30 m asl, 6.x.2023, A.B.S. Farias & J.C. Santos leg.). Additionally, we provide information on its biology, ecology, and taxonomic notes, along with illustrations of the collected males.